Superconductivity tuned through magnetic irreversibility in two-dimensional Co/Nb/Co trilayers under a parallel magnetic field - Stamopoulos, D.; Aristomenopoulou, E. (JOURNAL OF APPLIED PHYSICS, 2014)
In ferromagnetic/superconducting (FM/SC) planar hybrids, a reentrance of the upper-critical field line H-c2(T) is observed close to T-c. The effect is generally ascribed to the so-called domain-wall superconductivity and has been theoretically explored in great detail. Experimental investigations are limited mostly to FM/SC bilayers in which the FM layers host out-of-plane magnetic domains of strong anisotropy and large width (>300 nm), the SC layer is quite thick (>30 nm), and the external magnetic field was applied normal. To expand our knowledge to until now unexplored conditions, we study a series of Co(d(Co))/Nb(d(Nb))/Co(d(Co)) trilayers under a parallel magnetic field; Co outer layers exhibit out-of-plane magnetic domains of weak anisotropy and small width (<150 nm) and the Nb interlayer is very thin (<20 nm). We demonstrate a strong reentrance of H-c2(T) that can be tuned through the irreversible magnetization processes of the FM outer layers, the two-dimensional character of the SC interlayer, and the matching between the interfering SC and FM length scales. These results refine the nature of the reentrance of H-c2(T) in FM/SC hybrids and can motivate new theoretical and experimental investigations. (C) 2014 AIP Publishing LLC.